Kebijakan dan Regulasi Spionase Siber di Indonesia - Sodiq, Mohamad Djafar; Supono, Supono; Hendri, Fahzal; Ningsih, Eci Marisna (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Cyber espionage is an illicit activity that utilizes the internet network to monitor other entities by penetrating their computer networks. This research aims to provide a comparative explanation of the policies and regulations related to cyber espionage implemented in Indonesia and Germany. This research uses normative legal research methods with a statutory and regulatory approach, case studies, as well as comparative law (comparative approach) with a problem formulation of what policies and regulations related to cyber espionage are implemented in Indonesia and Germany? The results of this research show that Indonesia is showing strength in cyber security, characterized by increasing awareness of cyber security issues, its leadership role in Southeast Asia in this domain, and its rapid digital transformation that is driving the adoption of further levels of cyber security measures. However, Indonesia is grappling with various challenges such as a lack of skilled cybersecurity professionals and limited resources to implement a comprehensive cybersecurity strategy, as well as a legal and regulatory framework that requires continuous refinement and adaptation. In contrast, Germany's strong legal framework acts as a bulwark against cyber threats. Coupled with substantial technical expertise and an innovative approach to cyber security, Germany benefits from a transparent legal framework that ensures clarity and efficiency in dealing with cyber threats. Nonetheless, Germany also faces weaknesses, such as reliance on external technology and supply chains, the prevalence of sophisticated cyber threats, and the challenge of harmonizing cybersecurity practices across sectors